Smart Flood Monitoring System via IoT Platform for Early Warning of Road Closures Against Flood Events - Zainal, Zulaikha Aina; Farhana Ahmad Po'ad, (Evolution in Electrical and Electronic Engineering, 2024)
Floods constitute a recurrent natural disaster impacting Malaysia and various global regions annually. This project concentrates on conceiving and executing an Internet of Things (IoT)-based smart flood monitoring system, with the objective of furnishing early warnings and notifications about road closures during flood events. Presently, authorities resort to manual methods, such as employing stakes to assess water levels on roads. However, this project aspires to institute a more effective system, obviating the necessity for manual measurements, allowing authorities to receive water depth warnings promptly. The principal goal is to harness IoT technology, specifically through the Blynk application, to formulate a user-friendly approach for authorities to monitor potential flood-prone road areas. For this purpose, the system relies on vital data, notably water levels, to discern increases during flood events. The Smart Flood Monitoring System through an IoT Platform for Early Warning of Road Closures Against Flood Events utilizes electronic components, particularly the Ultrasonic sensor and Durian UNO embedded controller, to emulate traditional measurement techniques. The Ultrasonic sensor assesses the flood level, transmitting data to the Durian UNO. The Durian UNO plays a pivotal role, incorporating an integrated Wi-Fi module (ESP-01) for data transmission to the Blynk application, facilitating real-time flood level monitoring. The project also encompasses a user-friendly prototype to enhance device usability. Testing encompasses both indoor and outdoor water level detection. The results indicate that the ultrasonic sensor method accurately measures flooded road water levels with a precision of 96.65%. This system empowers authorities to promptly announce vehicle restrictions or road closures in response to flooding.